Conditional probability - rules of probability, Mathematics

Conditional probability - Rules of Probability

This is the probability associated with combinations of events but given that some prior result has already been achieved with one of them.

It's expressed in the form of

P(x|y) = Probability of x given that y has already occurred.

P(x|y) =  P(xy)/P(y) → conditional probability formula.

Illustration

In a competitive examination 30 candidates are to be chosen.  In all 600 candidates appear in a written test, and 100 will be call for the interview.

(i) What is the probability that a person will be called for the interview?

(ii) Find out the probability of a person getting chosen if he has been called for the interview?

(iii) Probability that person is called for the interview and is chosen?

Solution:

Assume event A be that the person is called for the interview and event B that he is chosen.

(i) P(A) = 100/600  = 1/6 

(ii) P(B|A) =  30/100 = 3/10

(iii) P(AB) = P(A) × P(B|A)

=  (1/6) * (3/10) = 3/60 = 1/20

Posted Date: 2/19/2013 8:11:51 AM | Location : United States







Related Discussions:- Conditional probability - rules of probability, Assignment Help, Ask Question on Conditional probability - rules of probability, Get Answer, Expert's Help, Conditional probability - rules of probability Discussions

Write discussion on Conditional probability - rules of probability
Your posts are moderated
Related Questions
solve and graph the solution set 7x-4 > 5x + 0

Hi I have a maths question related to construction as its a construction management course...i could send some example sheets too...could it be done?

Divides a given line-segment externally in the ratio of 1:2 Construction: i )Draw BX making an actueangle at B. ii) Starting from B, mark 2 equal points on BX as shown in the f


What fraction of the full price will you pay for 2 shirts? 3 4 11 2 $45.001 2 .

HOW WE CAN FACTORISE 12X+7X+1


Verify Liouville''''s formula for y "-y" - y'''' + y = 0 in (0, 1) ?

Proof for Properties of Dot Product Proof of u → • (v → + w → ) = u → • v → + u → • w → We'll begin with the three vectors, u → = (u 1 , u 2 , ...

1. Discuss lyapunov function theory and how it can be used to prove global assmptotic stability of solutions.(Give an example form natural and engineering sciences.) --- Draw le